Technological transformation of digital competence in the service sector - Denys Lykhopok (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
Technological transformation of society raises increased requirements for consumers’ readiness to use services, particularly in the social sphere, in a new digital format. Gradual digitalization of all aspects of socio-economic interaction creates new challenges for both service providers and their consumers. Digitalization processes require rethinking traditional approaches to interaction between market participants and the formation of new competencies. The paper presents theoretical and methodological approaches to defining fundamental concepts such as “digital literacy” and “digital competence” and examines the features of digital transformation in the services sector, taking into account consumer interests and the impact of digitalization on service accessibility for different population groups. A conceptually new author’s concept of “digital maturity” of social services consumers is introduced, which allows for a comprehensive assessment of not only cognitive and technical readiness, but also the functional capabilities of consumers to receive the full spectrum of services in digital form with maximum efficiency. This concept goes beyond the traditional understanding of digital literacy and forms an integrated indicator of readiness to function in a digital environment, taking into account dynamic changes in the technological landscape. It is substantiated from the standpoint of systems analysis that the necessary level of consumer digital maturity for comfortable consumption of social services depends on a multitude of interconnected factors: the current state of the social sphere whose services the consumer plans to use, the achieved level of automation and digitalization of business processes in the corresponding sector, as well as the duration of information-network communication in the service delivery process. The relevance of this research is significantly enhanced by contemporary global challenges, particularly pandemic restrictions, which accelerated the pace of digitalization and exacerbated the problem of digital inequality among different population groups, revealing insufficient readiness of consumers to use digital services.